Waist Structure Design and Dynamics Analysis of Humanoid Robot - Meng Zheng; Yankai Hu; Heng Li; Beilin He (Jixie chuandong)
In view of the simple structure of the robot in the current market and the fact that each joint is driven by a servo motor， a humanoid robot with a dodge function is designed， which is driven by a single motor and controls the state of the electromagnetic clutch to realize the movement of the lumbar joint. And finally the dodge motion of robot is completed. In order to verify the correctness of the main component selection and the rationality of the structural design， the dynamics of the robot trunk structure is studied by using the Lagrangian Function， and then the dynamics simulation analysis of the robot virtual prototype is performed by using ADAMS software， the corresponding joint torque curve is obtained. Finally， the robot physical assembly is completed and the dodge function is verified through experimental test.